Dietary adherence and cognitive performance in older adults: insights from a nationwide survey in China - Fan, Yameng; Yu, Yan; Tan, Jiao; Ma, Yonghong; Men, Ke (Frontiers in Nutrition, 2025)
BackgroundDietary guidelines, integrating the latest scientific evidence with traditional dietary culture, are regularly issued to provide dietary recommendations and promote health. However, the relationship between adherence to dietary guidelines and cognitive health has yet to be fully elucidated. In this study, we specifically examine the association between adherence to the Dietary Guidelines for Chinese (DGC) and cognitive performance among older adults.MethodsWe analyzed data from the China Health and Nutrition Survey (CHNS) (2011 and 2015), including participants aged ≥60 years. Adherence to the DGC was assessed using the Chinese Healthy Eating Index (CHEI). Cognitive performance was evaluated across the following three domains: (1) memory (immediate and delayed recall), (2) attention/executive function (counting backward from 20), and (3) processing speed (serial 7 subtraction). A composite z-score was derived to represent global cognition. Multivariate logistic regression and restricted cubic spline models were used to assess associations.ResultsAmong 2,174 older adults, higher CHEI scores were significantly associated with better performance at counting backward (attention/executive function, p < 0.05), serial 7 subtraction (processing speed, p < 0.01), and global cognition (p < 0.01). A significant interaction effect was observed between the CHEI and nationality in relation to cognitive performance (pinteraction <0.05). Among the 17 CHEI components, only adherence to the recommended intake of fish and seafood (OR: 0.55; 95% CI: 0.37, 0.82) was independently linked to better cognitive performance. Sensitivity analyses excluding individuals with diabetes or overweight or obesity, and treating cognitive performance as a continuous outcome yielded consistent results (p < 0.05).ConclusionGreater adherence to the DGC was associated with better cognitive performance, particularly in processing speed and attention/executive function. Promoting adherence to dietary guidelines may be a viable strategy for preserving cognitive health in aging populations.